2023
DOI: 10.1021/acsami.3c04260
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Prediction of Preterm Birth in Patient Plasma with Machine-Learning-Guided Raman Spectroscopy and Metabolomics

Lilly Synan,
Saman Ghazvini,
Saji Uthaman
et al.

Abstract: Preterm birth (PTB) is the leading cause of infant deaths globally. Current clinical measures often fail to identify women who may deliver preterm. Therefore, accurate screening tools are imperative for early prediction of PTB. Here, we show that Raman spectroscopy is a promising tool for studying biological interfaces, and we examine differences in the maternal metabolome of the first trimester plasma of PTB patients and those that delivered at term (healthy). We identified fifteen statistically significant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
2
1
0
Order By: Relevance
“…In our previous work focused on Raman spectral analysis of pregnant patient plasma samples who had preterm birth, we also observed similar tends in AAs. 28 Metabolic rewiring in AAs also contributes to disrupted protein synthesis and corroborates with the statistically significant decrease we observe in amide III peak at 1243 cm −1 (Figure 3m ) that represents proteins and type I collagen. Indeed literature evidence shows that in preeclampsia multiple closely‐packed proteomic pathways within the protein networks and corresponding gene expression are simultaneously dysregulated.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In our previous work focused on Raman spectral analysis of pregnant patient plasma samples who had preterm birth, we also observed similar tends in AAs. 28 Metabolic rewiring in AAs also contributes to disrupted protein synthesis and corroborates with the statistically significant decrease we observe in amide III peak at 1243 cm −1 (Figure 3m ) that represents proteins and type I collagen. Indeed literature evidence shows that in preeclampsia multiple closely‐packed proteomic pathways within the protein networks and corresponding gene expression are simultaneously dysregulated.…”
Section: Resultssupporting
confidence: 88%
“…We observed a similar trend in carotenoids in preterm labor pregnancies relative to healthy suggesting the important role of β‐carotene during pregnancy. 28 We also observed that sugar levels (848 cm −1 , Figure 3e ) are higher in preeclampsia cohort in all three trimesters relative to healthy. Indeed, there is a strong relationship between abnormal glucose metabolism and hypertension during pregnancy, and preeclamptic patients often have higher blood glucose levels that are exaggerated closer to term.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation